Immunological features in anti-U1-ribonucleoprotein antibody positive patients with systemic scleroderma - R. U. Shayakhmetova; L. P. Ananyeva; O. A. Koneva; M. N Starovoitova; O. V. Desinova; O. B. Ovsyannikova; L. A. Garzanova (Современная ревматология)
In anti-U1-ribonucleoprotein (anti-U1-RNP) antibody positive patients with systemic scleroderma (SSD), the clinical picture and course of the disease have specific features: there is a preponderance of its limited form; inflammatory damage to the joints and muscles comes to the fore; and cutaneous manifestations are mild. Moreover, a high frequency (68%) of interstitial lung disease is found. At the same time, the autoimmune profile in this group has been little studied.Objective: to investigate the level of major autoantibodies (autoAbs) in anti-U1RNP antibody positive patients with SSD and to compare the frequency of the autoAbs in this group and in the groups of patients with SSD phenotypes associated with anti-centromere antibodies (ACA) and anti-topoisomerase I (anti-Scl70) antibodies.Patients and methods. The investigation enrolled a total of 144 patients meeting the 2013 ACR/EULAR SSD classification criteria. Forty-four anti-U1RNP antibody positive patients were found to have autoAbs, rheumatoid factor (RF), anti-cyclic citrullinated peptide (ACCP), anti-Ro, anti-La, anti-double-stranded DNA (anti-dsDNA), anti-Smith (anti-Sm), anti-cardiolipin (aCL), anti-histidyl tRNA synthetase (anti-Jo1), anti-Scl70, and anti-RNA polymerase III (anti-RNAP-III) antibodies, and ACA in two points. The study group (anti-U1RNP antibody positive patients with SSD) and the comparison groups (anti-Scl70 and ACA positive patients) were comparatively analyzed.Results and discussion. Anti-U1RNP antibody positive patients with SSD were commonly observed to have overlaps (34%) with rheumatoid arthritis and systemic lupus erythematosus, as well as concurrence with Sjögren’s syndrome (SS) (32.5%). The study group was found to have frequently RF (27%), anti-Ro (41%), anti-dsDNA (50%) antibodies, rarely anti-Sm (9%), ACCP (9%), anti-La (7%), ACA (11%), anti-Scl70 (9%), and aCL (2%) antibodies. Anti-Jo1 and anti-RNAP-III antibodies were not detected in any patient. SSD patients who were highly positive for anti-U1RNP antibodies (more than 2 upper limits of the reference range) significantly more frequently exhibited RF, anti-Ro and anti-dsDNA antibodies (p<0.01). Over time, anti-U1RNP antibodies detected at the onset of the disease persisted in 75% of patients. autoAbs were observed to disappear in patients with a low baseline titer of anti-U1RNP antibodies. Re-examination demonstrated that the detection rate of other autoAbs remained high in the group of patients who were highly positive for anti-U1RNP antibodies. Comparison of the three groups showed that the specific feature of the study group was the more frequent presence of other autoAbs, among which anti-Ro antibodies were most important. Their presence was associated with SS.Conclusion. In addition to clinical features, patients with SSD and anti-U1RNP antibody overproduction differ from those with major SSD phenotypes by the more frequent presence of other autoAbs. Persons who are highly positive for anti-U1RNP show the steady-state elevated levels of RF, anti-Ro and anti-dsDNA antibodies and the rare detection of SSD-specific autoAbs (ACA, anti-Scl70 and anti-RNAP-III).